GERAKAN ORGANISASI PEREMPUAN INDONESIA DALAM BINGKAI SEJARAH - Mursidah Mursidah (UIN K.H. Abdurrahman Wahid Pekalongan, 2012)
Abstract : Feminism movement comes forward in various parts of the world, including in Indonesia. This movement pictures a woman in the position of the oppressed, and sistematically subordinate and ideologically imprisoned. In order toÂ release from the oppression, then, it has emerged in the history of some women's movement in Indonesia, in which women have moved forward and more focused in the improvement of the social position of women in marriage and family, and to improve the skills as a housewife by improving the education and the teaching as accompanied by an increase in skill. Abstrak : Gerakan Feminisme datang ke depan di berbagai belahan dunia, termasuk di Indonesia. Gerakan ini menggambarkan seorang wanita di posisi tertindas, dan sistematis bawahan dan ideologis dipenjara. Untuk melepaskan dari penindasan, saat itu, muncul dalam sejarah gerakan beberapa perempuan di Indonesia, di mana perempuan telah bergerak maju dan lebih fokus dalam peningkatan posisi sosial perempuan dalam perkawinan dan keluarga, serta meningkatkan keterampilan sebagai ibu rumah tangga dengan meningkatkan pendidikan dan pengajaran sebagai disertai dengan peningkatan keterampilan.Â